Peran Komunitas Kedai Baca Jenny dalam Menumbuhkan Minat Baca dan Kreativitas Masyarakat - Nasrullah Nasrullah (Jurnal Pustaka Ilmiah, 2022)
The reading interest of the Indonesian people is the lowest in ASEAN. The government and society should pay more attention to the crisis of culture and interest in reading in Indonesia. One of the efforts realized by the government and the community is to establish various kinds of reading places for the Indonesian people, one of which is the Jenny Bookstore Community Reading Garden. This study aimed to determine the role and constraints of Jenny's bookshop community in developing the people's interest in reading. This study used descriptive methods and by qualitative approach. The data in this study was collected by observation, interviews, and documentation. Based on the research results, it was known that Jenny's bookstore is a place to meet and exchange ideas with library concepts. Programs or activities carried out by Jenny's bookstore in developing people's interest in reading were established some program like KBJamming, menangisi akhir pekan, sajakkan saja, buka buku, books publishing, and happy stage program. The obstacles faced in growing people's interest in reading were operational funds, limited room, and lack of volunteers.